Using Trusted Intermediaries to Communicate Environmental Issues Across Security Forces. Issue 1 (2nd January 2022) - Jalili, Duraid
ABSTRACT: Militaries generate globally significant climate and biocapacity damage in both peacetime and wartime. This scenario is historically underpinned by organisational and socio-psychological barriers, resulting in military strategies that cancel out the gains borne of ongoing investments in energy efficient technologies. Yet, there are promising signs of a shift across various armed forces, with military personnel seeking greater knowledge and action on today's converging environmental crises. Targeted education represents a potentially significant pathway for supporting security personnel to drive evidence-based mitigation and adaptation initiatives leading to significant environmental gains. As this commentary highlights, the ability for experts across different disciplines and sectors to contribute to this process is becoming easier, due to a growing number of trusted intermediaries working to drive greater environmental awareness across the security sector.